Detection and analysis of low level tritium in rainwater for a proposed environmental monitoring program - Gillis, Jessica McDonnel, author; Brandl, Alexander, advisor; Whicker, Ward, committee member; Collett, Jeffrey L., committee member (Colorado State University. Libraries, 2014)
Radioactive tritium, an isotope of hydrogen, is present at low levels in the atmosphere and can be deposited by precipitation. Tritium is produced naturally by the interaction of cosmic rays with gaseous atoms in the atmosphere, but the primary contributors to atmospheric concentrations are residues from past nuclear weapons testing and releases of tritium produced at nuclear facilities. The National Atmospheric Deposition Program (NADP) is a nationwide program that manages and analyzes rain and snow samples from networks of precipitation monitoring stations. The NADP and Savannah River National Laboratory have jointly proposed a monitoring program for tritium in rainwater in order to demonstrate the use of existing sampling locations in the NADP's National Trends Network and characterize the deposition of radionuclides in the United States. This research investigates the feasibility of measuring tritium concentrations in rainwater samples given the proposed laboratory detection range of 0.6-1.2 Bq/L. Rainwater samples were analyzed using Colorado State University's liquid scintillation counter (LSC), and minimum detectable activity concentrations on the LSC were investigated based on background count rate, count duration, and detection efficiency. To achieve the analytical capabilities and throughput proposed, count times of several hours and comparison with tritium-depleted blanks were determined to be necessary. Detection efficiencies for tritium in rainwater were affected by quench in the samples, optimization of the counting window, and LSC vial type.